Cigarette Packaging as a Commercial Determinant of Smoking: A Thematic Analysis of Filipinos’ Perception of Graphic Health Warnings and Plain Packaging in the Philippines - Amul, Gianna Gayle H (Archīum Ateneo, 2025)
In line with recommendations of Article 11 of the WHO Framework Convention on Tobacco Control, the Philippines has implemented graphic health warnings (GHWs) on cigarette packs. While the Graphic Health Warnings Law was passed in 2014, it was only implemented in 2016. Using a commercial determinants of health framework, this study aims to contribute evidence on Filipinos’ perceptions of GHWs and the potential plain packaging of tobacco products in the Philippines. We used a dataset based on open-ended questions in online and nationwide household surveys from 2021. Data collectors showed mock-up sets of cigarette packs based on the Philippines' law on GHWs and Thailand's and Singapore's plain packaging to respondents to gather their comments on each pack's features and its GHW. We conducted a thematic analysis to extract themes in respondents' perceptions. We gathered 3,723 responses from online and household surveys. Most respondents commented on the Philippine packs' ineffectiveness and lauded GHWs from Singapore and Thailand for their characteristics and the information in the warnings, remarking that valuable features of Singapore and Thailand's plain packs for making current cigarette packaging more effective were larger GHWs, less brand visibility, and quitline availability. The study supports recent literature assessing local GHWs. Current GHWs are seen as ineffective, highlighting the need for policy reform. Policymakers should consider prohibiting single-stick cigarette sales, adopting plain packaging with larger GHWs to decrease brand visibility, and increasing the visibility and accessibility of quitlines to motivate smokers to quit and discourage Filipinos from smoking.